Do Firms' Product Lines Include Too Many Varieties, and Do Shops Open Too Many Days? - Klemperer, P; Padilla, A (CEPR, 1993)
This paper attempts to give a meaning to the empty concept of subsidiarity. It examines various kinds of government activity with respect to the optimal layer of government in Europe at which these activities should be performed. The paper criticizes Europe's industrial policies and its protectionism, and it points to European-wide public-goods and redistribution problems which make centralized government actions a matter of necessity. The paper's main focus is on the free movement of goods, capital, labour and services. It is argued that these movements will induce a process of fierce fiscal competition in which an inverse redistribution from the poor to the rich will emerge, where consumer protection becomes eroded and environmental standards are overdrawn.